The Effect of Using Inquiry Model on Science Process Skills and Student Learning Outcomes - Fahmi; Hery Fajeriadi; Yudha Irhasyuarna; Yuyun Eka Yulianti; Muhammad Kusasi (Jurnal Penelitian Pendidikan IPA, 2024)
Science learning must be changed by applying real and active science process skills which are shown by students being able to understand the use of tools, methods, and procedures and apply them in the discovery process and communicate them based on the evidence they get. The purpose of this study was to see the impact of the use of the inquiry model on science process skills and student learning outcomes. The research method used is a combination of quantitative and qualitative methods designed using a pre-test-post-test control group. The samples of this research were 7th-grade junior high school students. The length of the research process is 12 weeks. The results showed that there were significant differences between the two groups. This indicates that the inquiry model has a positive impact on students' science process skills. This was also accompanied by positive results on student learning outcomes in the group using the inquiry model. The conclusion is that quantitatively the fact that the inquiry learning model can improve science process skills and student learning outcomes is found. Optimizing the application of this model is needed to support progress in the education quality.